Implementasi Metode AHP-TOPSIS Dalam Menentukan Prioritas Perbaikan Jalan di Kabupaten Malang - Refal Ade Pratama; Wahyudi Harianto (SMARTICS Journal, 2021)
Indonesia as a developing country makes Indonesia prioritize infrastructure development. One of them is the highway. The provision of good road infrastructure is very important especially in Malang Regency. Programs for road repair and maintenance are often not well targeted, of course this can be detrimental, especially to the budget provided by the government. In this case, the government must have a system to determine road repair priorities. There are 5 criteria in consideration of decision making, namely 1) the percentage of good, 2) the number of sub-districts traversed, 3) access to roads, 4) daily traffic and 5) the number of residents per sub-district. The methods that can be used in the decision support system are Analytical Hierarchy Process (AHP) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). These methods will be combined where AHP is used for the weighting of the criteria and TOPSIS for the ranking of alternatives. In the calculations carried out by the system that has been successfully designed and built, the system has functioned properly and can determine road repair priorities based on alternative rankings.